(untitled) (Damascus University Journal for legal sciences, 2022)
International impediments to liability exempt a state that has committed an unlawful or internationally prohibited act from its international responsibility as a result of committing it under certain circumstances or situations (despite the availability of the conditions for establishing this responsibility, represented in the presence of an internationally wrongful act and the existence of harm, as well as the proportion of this act to a specific state and the absence of one The obstacles to this responsibility, represented in consent, reciprocity, countermeasures, and finally the state of necessity, which turns this illegal act into an internationally permissible act). Accordingly, this research will shed light on the state of necessity (which is of great importance at the international level, as it is the state through which the state resorts to committing an unlawful act to pay a danger without assuming responsibility for this action), in two axes, the first of which is devoted to talking about the concept of the state of necessity (Its definition and distinguishing it from similar terms). As for the second axis, I devoted it to clarifying the position of international jurisprudence, and international law commission on it.